Evidence System of Counting Elements of State Loss Against Corruption Criminal Actions in Indonesian Criminal Jurisdiction System - M. Rizal Bagaskoro; Jawade Hafidz (Law Development Journal, 2021)
This study seeks to answer the problem of what is the legal problem in the process of proving the calculation of elements of the State Financial Loss on Corruption? And what is the solution to legal problems in Evidence of Calculation of Elements of State Financial Losses on Corruption in the Criminal Justice System? Research for is normative research. Based on the research, it can be concluded that the problems of the legal system are related to the substance of the law in law enforcement on corruption which is detrimental to state finances and problems in the legal system related to the legal structure in law enforcement in criminal acts of corruption that are detrimental to state finances.